Pengaruh Media Pembelajaran Terhadap Motivasi Belajar Siswa pada Mata Pelajaran Matematika di Sekolah Dasar - Ade Mustika Andari; Zubaidah Amir; R. Risnawati; Mhmd Habibi (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
Growing student motivation is one of the techniques in developing the ability and willingness to learn. The purpose of this study was to determine the effect of instructional media on students' learning motivation in mathematics in elementary schools. This type of research is "ex post facto" with a research design using a one-shot case study. The subjects in this study were class IV students at SDN 028 Kubang Jaya class A and B, each of which had 15 students. The sampling technique uses non-probability sampling, namely purposive sampling. The research instruments used were observation and questionnaires. The data analysis technique uses product moment correlation with the help of SPSS 23. SPSS analysis of the product moment correlation shows the significance level of sig. (2-tailed) = 0.531, it can be concluded that the two variables are included in the "enough" category. From this analysis it can be concluded that there is an influence of learning media on learning motivation of 28.19%, other variables not mentioned in the study reach 71.81%.